Don Chisciotte e Sancio Panza - Grimaldi, Giovanni, 1917-2001; Franchi, Franco, 1928-1992; Ingrassia, Ciccio, 1922-2003; Cervantes Saavedra, Miguel de, 1547-1616.; Claudia Cinematografica; Video Mercury Films, S.A. ([Rome, Italy] : Claudia Cinematografica, 1968)
In this comic version of the famous Man of la Mancha by Miguel de Cervantes, Don Quixote decides to imitate the exploits of knights-errant described in epics. Thoroughly equipped and followed by his faithful squire Sancho Panza, he sets out in search of that glory evoked in books, running to the defense of the weak and oppressed and fighting all forms of injustice.
Originally produced as a motion picture in 1968.
Based on: Don Quixote / Miguel de Cervantes.
Franco Franchi, Ciccio Ingrassia, Fulvia Franco, Umberto D'Orsi, Mirella Pamphili, Franco Giacobini, Liana Trouche, Ivan Scratuglia, Paolog Carlini.
Cinematographer, Mario Capriotti; editor, Amedeo Giomini; music, Lallo Gori.
Dubbed into Spanish.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed December 30, 2015).
Keywords: Don Quixote (Fictitious character) -- Drama; Panza, Sancho (Fictitious character) -- Drama; Dulcinea (Fictitious character) -- Drama; Knights and knighthood -- Spain -- Drama; Chivalry -- Drama; Quests (Expeditions) -- Drama; Spain -- Social life and customs -- 16th century -- Drama; Comedy films; Parody films; Film adaptations; Feature films; Internet videos; Streaming video